COMPARISON OF EFFICACY OF TAZAROTENE/BETAMETHASONE VERSUS CALCIPOTRIOL/BETAMETHASONE IN PATIENTS WITH MILD TO MODERATE PLAQUE PSORIASIS - AMIN, S; KHAN, MR; SALEEM, M; KHAN, A; MUSHTAQ, F (Biological and Clinical Sciences Research Journal, 2024)
Plaque psoriasis is a chronic inflammatory skin disorder that significantly impacts patients’ quality of life. Combination therapies, such as Tazarotene/Betamethasone and Calcipotriol/Betamethasone, are widely used for its management. Evaluating the efficacy of these combination therapies is essential for optimizing treatment outcomes. Objective: To evaluate the efficacy of Tazarotene/Betamethasone compared to Calcipotriol/Betamethasone in patients with mild to moderate plaque psoriasis. Methods: Following ethical committee approval, this randomized comparative study was conducted in the Department of Dermatology, PIMS, Islamabad, from January 2024 to June 2024. One hundred seventy patients with mild to moderate plaque psoriasis were enrolled and randomly assigned to two groups. Group A received Tazarotene 0.045% cream combined with Betamethasone dipropionate 0.05% ointment, while Group B was treated with Calcipotriol 0.005% combined with Betamethasone dipropionate 0.05% ointment. Both therapies were applied once daily for 12 weeks. The treatment response was assessed by evaluating changes in the Psoriasis Area and Severity Index (PASI) scores and Body Surface Area (BSA) affected. Data were analyzed using SPSS Version 26, and comparisons between the groups were made using t-tests, with significance set at p < 0.05. Results: The mean age of participants was 39.52±11.07 years. In Group A, 35.3% were male and 64.7% were female, while in Group B, 41.2% were male and 58.8% were female. Baseline PASI scores and BSA affected were comparable between the groups. After 12 weeks, Group A showed a more significant reduction in PASI scores (4.72±1.01 vs. 5.20±0.93, p=0.00) and BSA affected (3.49±0.86% vs. 4.21±0.86%, p=0.00) compared to Group B. Conclusion: Both combination therapies resulted in significant improvements in PASI scores and reductions in BSA affected. However, Tazarotene/Betamethasone was more effective than Calcipotriol/Betamethasone, likely due to the keratolytic properties of Tazarotene. These findings suggest that Tazarotene/Betamethasone may offer superior efficacy in managing mild to moderate plaque psoriasis.